Forced Divorce Polemic: Comparative Analysis of the Hanafi and Shafii Schools of Thought - Muhammad Nirwan Idris; Kurnaemi Anita (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This article aims to summarize the views of the Hanafi and Shafii madhhabs regarding the status of divorce of a person who is forced and the method of determining it, as well as to find out the method of scholars in tarjīḥ opinion between the Hanafi and Shafii schools in this case. To get answers to the problems, this article uses library research that focuses on manuscript and text studies, using case and comparative approach methods. By looking at some coercive ḍawābiṭ, the results of the study found that; First, the Hanafis argue that divorce imposed by a person who is forced is legal, because here he faces two tough choices, namely divorcing his wife or receiving threats from the person who forced him, and in fact, he chooses to divorce his wife. In contrast to the Shafii school of thought, which is not consider valid, because divorce is an absolute right for the husband alone, also because Allah has aborted disbelief in those who are forced to disbelieve. The istinbāṭ method of the law used by the Hanafi and Shafii schools is that they both use kias. Second, the scholar's method in tarjīḥ the opinion between the Hanafi school and the Shafii school regarding forced divorce is by looking at the sanad hadith. In this case, the majority of scholars further strengthen the hadiths used as evidence by the Shafii school because they see the ṡīqāh (trusted) narrators of hadith so that all of their narrators can be used as evidence.